May progesterone receptor membrane component 1 (PGRMC1) predict the risk of breast cancer?. (2nd January 2016) - Zhang, Ying; Ruan, Xiangyan; Willibald, Marina; Seeger, Harald; Fehm, Tanja; Neubauer, Hans; Mueck, Alfred O.
Abstract: Objective : Our and other studies have pointed on an important role of progesterone receptor membrane component 1 (PGRMC1) in development of breast cancer, especially in hormone therapy. To investigate if PGRMC1 could be used to predict the risk for getting breast cancer, we assessed in tissues of patients with primary invasive breast cancer, if the expression of PGRMC1 may be associated with the expression of estrogen receptor alpha (ERα), progesterone receptor (PR), and ki67. Methods : Samples from 109 patients with breast cancer between the years 2008 and 2014 were obtained with the patients' consent. Each sample was evaluated for the ERα, PR, Ki67, and PGRMC1 expression by immunohistochemistry using serial sections from the ame paraffin block comparing malignant tissue to benign tissue. Results : Expression of PGRMC1 is increased in tumor area compared with non-cancerous tissue and positively correlates with ERα expression ( OR  = 1.42 95%CI 1.06–1.91, p  = 0.02). No association was obtained between expression of PGRMC1 and PR or Ki67. Conclusion : It can be suggested that women with breast epithelium highly expressing PGRMC1 and in interaction with ERα may have an increased risk to develop breast cancer, especially when treated with hormone therapy.